Antimicrobial Susceptibility and Characteristics of Neisseria gonorrhoeae Isolates from Puerto Rico, 2012-2017 - Scharbaai, Ramón; Serrano, Lilliana; Ortiz, Juliara E. (Puerto Rico Health Sciences Journal, 2024)
Objective: Monitoring the susceptibility patterns of Neisseria gonorrhoeae is essential for the continuing compliance with current treatment recommendations. Puerto Rico conducts susceptibility tests on N. gonorrhoeae; however, trends on antimicrobial resistance in the island have not been reported since the mid 80’s. Methods: We performed a secondary analysis of a national data repository on the antimicrobial susceptibility of N. gonorrhoeae isolates between 2012 and 2017; a period of time when the CDC recommended a single dose of ceftriaxone and azithromycin for the treatment of uncomplicated gonorrhea. Data on susceptibility to eight antibiotics using the standard disk diffusion method was obtained for 30.0% (84/276) of the samples collected from the Sexually Transmitted Disease clinics in Puerto Rico. We also performed patient demographic analyses linked to resistance. Results: Rates of resistance to ceftriaxone and azithromycin were 0% and 4.0% (2/50), respectively. The percentage of isolates resistant to antimicrobials no longer recommended in Puerto Rico, such as tetracycline, ciprofloxacin, and penicillin, was 86.0% (43/50), 76.0% (38/50), and 38.0% (19/50), respectively. Prevalence of resistant N. gonorrhoeae was higher among men who have sex with men, MSM (79%, 37/47). Discussion: Lack of resistance to ceftriaxone and slow emergence of azithromycin resistance was identified from 2012-2017. It is imperative to continue the surveillance for emerging patterns of resistance, especially for ceftriaxone, as it is part of the current treatment guidelines. Therefore, protocols for culture based surveillance, including sample transport and processing, should be strengthened to ensure quality assured epidemiology of gonococcal resistance in Puerto Rico.